Synthesis and characterization of omega-sulfonated polystyrene-stabilized cadmium sulfide nanoclusters - Jin, YH; Kim, J; Kim, SS (POLYMER SOC KOREA, 2004)
We report an important and useful method for preparing omega-sulfonated polystyrene-stabilized cadmium sulfide (CdS) nanoclusters. The omega-sulfonated polystyrene (M-n = 5000 g/mol) was prepared successfully through chain-end sulfonation of poly(styryl)lithium using 1,3-propanesultone; the resulting polymer was used successfully as a polymeric stabilizing agent for the preparation of semiconductor US nanoclusters by reduction of cadmium acetate in a mixture of toluene and methanol (9:1, v/v). The nanoclusters that formed were characterized by a combination of transmission electron microscopy, X-ray diffraction, and UV/Vis spectroscopic analysis. The omega-sulfonated polystyrene-stabilized US nanoclusters synthesized in this study exhibited the cubic phase (zinc-blende phase) structure in the range of 2similar to8 nm.
Keywords: SEMICONDUCTOR-POLYMER COMPOSITES; CDS NANOPARTICLES; METAL NANOPARTICLES; GOLD NANOPARTICLES; OPTICAL-PROPERTIES; ANIONIC SYNTHESIS; SIZE CONTROL; SURFACE; COLLOIDS; CLUSTERS